ANALISIS KONFLIK DAN PENGARUHNYA TERHADAP MUTU PENDIDIKAN DI RAUDHATUL ATHFAL (RA) AL-KAHFI KOTA MEDAN - Neliwati Neliwati; Sri Rahayu Nasution; Yulita Suyatmika; Muhammad Fuad Zaini (Universitas Indraprasta PGRI, 2022)
This study aims to analyze the conflict that occurred in RA Al-Kahfi, Medan City, and its effect on the quality of education. Analyze the conflicts that occur and the quality of conditions in RA. The research method used is a qualitative method by applying a case study approach. The results of the study are (1) the conflict that occurred in RA Al-Kahfi Medan (2) to improve the quality it is necessary to have the right strategy in empowering educational staff through cooperative cooperation, providing opportunities for educational staff to improve their profession. and encourage the involvement of all education personnel in various activities that support school programs, one of which is administration, teachers are able to manage themselves in carrying out learning process activities, teachers must have learning tools prepared before the learning process is carried out